Diversity of Mungbean Germplasms through See Protein Electrophoresis - Nath, D; Roychowdhury, B; Dasgupta, T; Mondal, N (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available.Key words: Mungbean; Seed Protein; electrophoresis Bangladesh j. genet. biotechnol. 6 (1&2): 15-17, 2005 (June & December)